Preparedness of Nurses in Handling Disaster Victims in Sulawesi Tengah - Alfrida Semuel Ra'bung; Rina Tampake; Sova Evie; Akbar Nur; Dg. Mangemba (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2024)
As a disaster-prone province, Central Sulawesi requires preparedness in disaster management. The role of nurses in disaster preparedness cannot be separated. The purpose of this study was to examine the readiness of nurses in disaster management in Central Sulawesi. This type of survey research with a correlational approach was carried out at the Palu City Government Hospital from June to August 2022. The research sample was nurses who worked in the hospital emergency room. 85 nurses who met the selection criteria to participate in this study were obtained by simple random sampling technique. The nurse's preparedness variable in handling disaster victims was measured using the Disaster Preparedness Evaluation Tool (DPET) questionnaire which was distributed through the Google form. Data analysis used product-moment correlation analysis and Spearman rank. The preparedness of nurses in dealing with disaster victims is in a good category (72.6%). There is a significant relationship between age (p = 0.001), length of work (p = 0.001), and training (p = 0.001) with the readiness of nurses in disaster management, while gender (p = 0.113) and education (p = 0.927) ) did not show a significant relationship. The preparedness of nurses in managing disaster victims is in the good range, and there is a correlation between nurses' preparedness in managing disaster victims and their age, length of employment, and training. Ongoing training in disaster management and practice with disaster victims should be given to nurses.